Understanding financial literacy and associated factors among adult population in a low-middle income country. Issue 6 (June 2022) - Van Nguyen, Ha; Ha, Giang Hai; Nguyen, Diep Ngoc; Doan, Anh Hai; Phan, Hai Thanh
Abstract: This study aims to identify whether demographics, socio-economic factors, the usage of the internet, smartphone and bank, and cultural factor affect Vietnamese adults' financial literacy. A sample of 669 participants participated in the online survey questionnaire (response rate of 89.92%). Multivariate general linear model regression shows that adults of younger age have better skills in cash management, credit management, savings and investment, and financial management compared to older adults. The findings suggest that participants with better income could manage savings and overall finance more effectively. Furthermore, respondents with "Uncertain avoidance" in the culture had better skills in cash management, saving, and investment. Meanwhile, preferring masculinity had higher scores in credit management, insurance, and total scale compared to those preferring femininity. The significant contribution of this study is its usefulness for economic players to have assertive financial strategies and policymakers to enhance the level of financial literacy and provide trustworthy financial guidance. Highlights: The level of financial literacy of Vietnamese adults is at an average level. Using financial management applications support higher financial literacy scores. People preferring uncertainty avoidance are more financially literate. Financial, educational programs are necessary for a sustainable financial life. Abstract : financial literacy; financial management behaviors; Vietnam population; cultural factors.